((x^2) + 2)y′′ + xy' − 3y = 0
"(x^2+2)y''+xy'-3y=0\\\\\n\\text{Let } t=\\sinh^{-1} (\\frac{x}{\\sqrt{2}})\\\\\n\\implies x=\\sqrt{2}\\sinh{(t})\\\\\n\\frac{dx}{dt}=\\sqrt{2}\\cosh{(t})\\\\\n\\implies \\frac{dt}{dx}=\\frac{1}{\\sqrt{x^2+2}}\\\\\n\\implies \\frac{d^2t}{dx^2}=\\frac{-x}{(x^2+2)^{\\frac{3}{2}}}\\\\\n\\frac{dy}{dx}=\\frac{1}{\\sqrt{x^2+2}}\\frac{dy}{dt}\\\\\n\\frac{d^2y}{dx^2}=\\frac{1}{x^2+2}\\left[\\frac{d^2y}{dt^2}-\\frac{x}{(x^2+2)^{\\frac{1}{2}}}\\frac{dy}{dt}\\right]\\\\\n\\text{Substituting into the original equation, we have }\\\\\n\\frac{d^2y}{dt^2}-3y=0\\\\\n\\text{Get the auxiliary equation}\\\\\nm^2-3=0\\\\\n\\implies m_1=\\sqrt{3}, m_2=-\\sqrt{3}\\\\\ny=C_1e^{\\sqrt{3}t}+C_2e^{-\\sqrt{3}t}\\\\\n\\text{But } t= \\sinh^{-1} (\\frac{x}{\\sqrt{2}})\\\\\n\\implies y(x)=C_1e^{\\sqrt{3}\\sinh^{-1} (\\frac{x}{\\sqrt{2}})}+C_2e^{-\\sqrt{3}\\sinh^{-1} (\\frac{x}{\\sqrt{2}})}"
Comments
Leave a comment